The Role of the Water Police in Maintaining the Stability of the Indonesian Maritime Economy - Sri Rahmawati Isnaini Ginting; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
Indonesia as a maritime country already has laws that regulate the economy and maritime affairs. However, criminal acts in Indonesian waters continue to occur, whether committed by foreign nationals or Indonesian citizens themselves. This can damage the ecosystem and the Indonesian marine economy will also be threatened with security. Therefore, the role of the marine police is needed in monitoring and maintaining the stability of the marine economy in Indonesia. This research is a descriptive qualitative research. With literature study data collection techniques through documents from existing cases. The results of this study indicate the importance of the role of the marine police in maintaining the stability of the Indonesian marine economy.